Examining the effects of problematic alcohol use on cigarette abstinence in recently diagnosed cancer patients enrolled in a cessation trial: A secondary analysis. (April 2021) - Streck, Joanna M.; Hyland, Kelly A.; Regan, Susan; Muzikansky, Alona; Rigotti, Nancy A.; Ponzani, Colin J.; Perez, Giselle K.; Kalkhoran, Sara; Ostroff, Jamie S.; Park, Elyse R.
Highlights: Most smoking clinical trials exclude those with problematic alcohol use (PAU). We investigated the impact of PAU on smoking cessation outcomes in cancer patients. Newly diagnosed cancer patients with PAU were not less likely to quit smoking. Cancer patients with PAU can benefit from an evidence-based cessation intervention. Abstract: Aims: Among people with cancer, dual alcohol and tobacco use increases risk for morbidity and mortality. Most smoking cessation clinical trials with this patient population have excluded individuals with problematic alcohol use. This investigation examined whether problematic alcohol use affects smoking cessation in cancer patients. Methods: Mixed-methods secondary analysis of data from the Smokefree Support Study, a randomized-controlled trial examining the efficacy of Intensive (IT; n = 153) vs. Standard Treatment (ST; n = 150) for smoking cessation in newly diagnosed cancer patients. Problematic alcohol use was assessed at enrollment using the Cut-Down-Annoyed-Guilty-Eye-Opener (CAGE), weekly frequency of alcohol use and binge drinking measures. Alcohol use was categorized as: no current alcohol use, moderate and problematic use. The primary outcome was biochemically-confirmed cigarette abstinence at 6-months. A subset of patients (n = 72) completed qualitative exit-interviews. Results: Among all participants, biochemically-confirmed cigarette abstinence rates were 25% (n = 32), 28% (n = 27), and 36% (n = 20) for participants reporting no current alcohol use, moderate use, and problematic use, respectively (p = 0.33). In logistic regression analysis, neither problematic alcohol use (AOR = 0.96, 95% CI = 0.35–2.67, p = .94) nor the problematic use by study arm interaction (AOR = 2.22, 95% CI = 0.59–8.39, p = .24) were associated with biochemically-confirmed 6-month abstinence. Qualitatively, participants reported that drinking alcohol triggers urges to smoke. Conclusion: Newly diagnosed cancer patients reporting problematic alcohol use were not less likely to quit smoking than those without. Additional research is needed to investigate whether problematic alcohol users may benefit from smoking and alcohol behavior change interventions at the time of cancer diagnosis.